Induced variability in morphological characteristics of Euphorbia fulgens Karw. ex Klotzsch - Pérez Nicolás, Mónica; Colinas y León, María Teresa; Alia Tejacal, Iran; Rodríguez Barbecho, Carlos; Peña Ortega, Margarita Gisela; De La Cruz Torres, Eulogio Cruz (Revista Mexicana de Ciencias Agrícolas, 2022)
Euphorbia fulgens is an ornamental species that, in Mexico, has little variability in the color of flowers, so this work had as an objective to evaluate the effect of 60Co gamma radiation on seeds and morphological characteristics of adult plants, as well as to obtain mutants of different colors in the flowers. Seeds were collected in communities of Oaxaca (M0), irradiated at nine doses (50, 100, 150, 200, 250, 300, 450, 600, 750 Gy) and established under greenhouse until the adult stage (M1), giving follow-up until the development of their offspring (M2). Emergence, survival and 27 morphological characteristics corresponding to vegetative and reproductive structures in both generations were evaluated. The percentage of emergence and the number of plants that survived decreased as the radiation dose increased. Radiation doses of 250 Gy or higher caused seed germination percentages to be less than 50%. The treatments produced differences in the variables: number of branches with inflorescences and color of petaliferous appendages. The dose of 300 Gy generated branched individuals with different inflorescence color, although it affected survival. The phenotypic distribution in progenitors and descendants was similar, showing differences in number of cymes, number of cyathia and color of petaliferous appendages. Irradiation is a suitable technique to generate variation in the color of the inflorescences in this species.
Keywords: color; gamma rays; induced mutagenesis; ornamental plant